Long-term efficacy and safety of sirolimus for retinal astrocytic hamartoma associated with tuberous sclerosis complex - Zhang, Chen-Xi; Xu, Kai-Feng; Long, Qin; Zhang, Xiao; Yang, Zhi-Kun; Dai, Rong-Ping; Zhang, Zhi-Qiao (Frontiers in Cell and Developmental Biology, 2022)
Mammalian target of rapamycin (mTOR) inhibitors (sirolimus or everolimus) have been demonstrated effective in reducing the size of tuberous sclerosis complex (TSC)-associated retinal astrocytic hamartoma (RAH) in short-term. To investigate the long-term efficacy and safety of sirolimus on TSC-associated RAH, 13 TSC-associated RAH patients (59 RAH lesions) who received sirolimus therapy for at least 2 years were retrospectively enrolled in this study. Changes in the maximal thickness (MT) of RAH on optical coherence tomography and longest base diameter (LBD) of RAH on color fundus photography were accessed. The results showed that for a mean follow-up of 39 months, sirolimus was associated with a mean reduction of 14.6% in MT and 6.8% in LBD of RAHs. The main impacts of sirolimus occurred within the first 6-12 months, with 14.8% reduction in MT and 4.7% reduction in LBD. Mouth ulceration（10 [76.9%]）and acne (9 [69.2%]) were the most common adverse events. These follow-up data support the long-term use of sirolimus in TSC-associated RAH patients, and persistent use of sirolimus possibly prevents tumor regrowth.